Recent developments to improve the quality and economics of testing for fatigue and fracture - Sunder, R. (Проблемы прочности, 2009)
We have developed a number oftechnologies aimed at rendering test equipment affordable and at the same time reliable and well-supported. These include technologies related to actuator servodrives, energy efficient pumps, modular control and instrumentation electronics and open-source software that is efficient in real-time operation.